(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2018)
Una sintetica contestualizzazione teorica degli interventi presentati al seminario “Teorie della narrazione a confronto” tenutosi all’Università Sapienza di Roma il 14 e 15 febbraio 2018. In this presentation, the readers will find a short theoretical contextualization of the interventions read on the occasion of the seminar “Teorie della narrazione a confronto”, held at Sapienza University of Rome on 14th and 15th February 2018.